When the Eustachian Tube Is Normal: Selective Epitympanic Dysventilation Syndrome in Primary Acquired Cholesteatoma – An Evidence-Based Case Report - Pratiwi, Dewi; Sudrajad, Hadi; Primadewi, Novi; Ramliana, Dienia Nop (Masters Program in Public Health, Sebelas Maret University, 2026)
Background: Primary acquired cholesteatoma is a benign yet locally destructive middle ear lesion with an incompletely understood pathogenesis. While Eustachian tube dysfunction is commonly implicated, it does not explain cases with normal middle ear pressure. Selective epitympanic dysventilation syndrome (SEDS) has been proposed as an alternative mechanism involving localized ventilation impairment within the epitympanum. This study aims to provide a clearer understanding of the clinical features of cholesteatoma associated with SEDS, which may help clarify its etiopathogenesis, support earlier detection, limit disease progression, and guide more appropriate, individualized clinical decision-making. Case presentation A 55-year-old female presented with one year of persistent, malodorous left otorrhea and progressive hearing loss over three months. Otoscopy revealed mucopurulent discharge with an attic perforation. Nasoendoscopy showed a patent Eustachian tube. Audiometry demonstrated mild conductive hearing loss (31.25 dB), and tympanometry showed a Type A curve, indicating normal middle ear pressure. Mastoid MSCT revealed opacification of mastoid air cells and antrum with intact ossicles and no mesotympanic involvement, suggesting a localized ventilation disorder consistent with SEDS. Conclusion: SEDS is an important and underrecognized mechanism in primary acquired cholesteatoma. Its recognition is essential for early diagnosis and for guiding surgical strategies that restore epitympanic ventilation to prevent recurrence.